Preparation and evaluation of rotigotine-loaded implant for the treatment of Parkinson's disease and its evolution study - Aiping Wang; Yanxiang Liu; Rongcai Liang; Xuemei Zhang; Kaoxiang Sun; Zimei Wu; Wanhui Liu (Elsevier, 2016)
Purpose: To develop rotigotine-loaded implants (RI) to achieve continuous release of rotigotine for long duration for the treatment of Parkinson's disease (PD). Methods: RI was prepared by hot-melt extrusion method using poly (lactide-co-glycolide) (PLGA) as the matrix. In vitro drug release was optimized by drug loading, melting temperature during preparing process and additives. The surface and internal morphology of RI was imaged by SEM. The in vivo release profile of RI was investigated on rat. Results: RI prepared with PLGA 7525 5A showed sustained release of 40 days while suffering a lag phase, which was significantly shortened by blending 5050 2A and mannitol in the matrix. RI prepared by 7525 5A/5050 2A/mannitol = 55:10:5 (rotigotine 30%) showed a 40-day sustained release in vivo with no lag phase. The drug release from RI was also affected by drug loading and melting temperature probably due to the drug state existed in the implant. The evolution of implants during release process was correlated well with the drug release kinetics. Conclusion: RI could achieve sustained drug release for 40 days which could supply an alternative of continuous dopaminergic stimulation (CDS) for the treatment of PD.